Factors Affecting Non-Compliance of Patients Taking Tuberculosis Medication in The Working Area of Health Services of Liquiça District, Timor-Leste, 2018 - Seixas da Cruz, Oscar (Jurnal KESANS : Kesehatan dan Sains, 2024)
Introduction: Non-adherence to taking tuberculosis medication is a patient who is unable or refuses to take tuberculosis medication based on a doctor's prescription, such as: taking inconsistent medication, inadequate clinic visits, inadequate dot program, refusing to take medication. Of the 1/2 million people diagnosed with mdr-tuberculosis, the rate of non-adherence to treatment is difficult to assess and it is estimated that more than a quarter of tuberculosis patients fail to complete treatment within 6 months. Method: The method used quantitatively with the cross-sectional study approach, the population is all tuberculosis patients who run the dots program including those who fail treatment, relapse, and return after defaulted with the age of more than >14 years as many as 142 patients, samples as many as 105. Data collection techniques use nominally scaled questionnaires. Result and Discusion: The test results of univariate and bivariate analysis of chi-square, bivariate analysis using a significant alpha value of 5% (?=0.05). The results of bivariate analysis showed that there was a significant influence between education level (rp = 3,420), knowledge level (rp = 3,052), family support (rp = 0,003), length of treatment (rp = 3,149), on the patient's inadequacy in taking tuberculosis drugs. Conclusion: In conclusion, the results of this study are the level of education, level of knowledge, family support, duration of treatment affect the non-compliance of patients taking tuberculosis drugs.